Visualisasi Pemetaan Co-Occurance Term dan Temporal Mapping dalam Tren Riset Sexual Education - Saputra, Aqmal Maulana; Hawa, Intan Mutiara (Griya Widya: Journal of Sexual and Reproductive Health, 2025)
Background: Previous bibliometric analyses tend to mix SE with reproductive health issues or are geographically limited. This study aims to fill this gap through exclusive bibliometric mapping of the topic of SE. Method: Bibliometric approach with quantitative network analysis design. Data were obtained from Google Scholar via Publish or Perish with a title-based search strategy using the phrase “Sexual Education”, resulting in 810 scientific articles in the range of 2000-2025. The analysis was conducted using VOSviewer through co-occurrence term mapping and overlay visualization for temporal analysis. Result: This study identified six gaps in SE research: (1) disparities in SE research in the policy domain and inclusion of vulnerable groups such as people with intellectual disabilities; (2) segmentation between protectionist (e.g., child sexual abuse) and pedagogical (CSE, curriculum) approaches; (3) marginalization of qualitative methods and systematic reviews; (4) narrow gender focus, limited to women's issues; (5) lack of studies of barriers and access in CSE implementation; and (6) lack of exploration of the effectiveness of SE programs in adolescent populations. Implication: The study results have practical implications for policy, education, and research, with key recommendations being the inclusive integration of CSE into the curriculum, cross-sector collaboration for evidence-based SE programs, and the use of bibliometric findings to fill identified research gaps. Novelty: Contributing to mapping SE research trends through bibliometrics, focusing on the analysis of key terms and their development, different from previous studies that expanded to other topics such as reproductive health and had certain population segmentations.